Effects of a School-Based Instrumental Music Program on Verbal and Visual Memory in Primary School Children: A Longitudinal Study - Roden, Ingo; Kreutz, Gunter; Bongard, Stephan (Frontiers in Neuroscience, 2012)
This study examined the effects of a school-based instrumental training program on the development of verbal and visual memory skills in primary school children. Participants either took part in a music program with weekly 45 minutes sessions of instrumental lessons in small groups at school, or they received extended natural science training. A third group of children did not receive additional training. Each child completed verbal and visual memory tests for three times over a period of 18 months. Significant Group by Time interactions were found in the measures of verbal memory. Children in the music group showed greater improvements than children in the control groups after controlling for children's socio-economic background, age and IQ. No differences between groups were found in the visual memory tests. These findings are consistent with and extend previous research by suggesting that children receiving music training may benefit from improvements in their verbal memory skills.